Mouse diet and vendor impact microbiome perturbation and recovery from early-life pulses of amoxicillin - Curtis-Joseph, Noelle; Peterson, Rachel; Brown, Claire E.; Beekman, Chapman; Belenky, Peter (Frontiers in Microbiomes, 2024)
The gut microbiome is a dynamic ecosystem shaped by various factors, including diet, sex, and environment. This system plays a crucial role in host health, such that perturbation in the form of antibiotics can lead to a vast array of negative outcomes. Accordingly, a growing body of work seeks to develop interventions to protect the microbiome during antibiotic exposure. While it is well established that antibiotics can disrupt the microbiome in the short term, how the impact of antibiotics is modulated by factors such as diet, sex, and environment is poorly understood. In this study, we analyzed how sex, diet and early life environment (vendor of origin) modulate the impact and recovery of the microbiome in mice treated with oral amoxicillin. Utilizing 16S rRNA gene sequencing and bioinformatic analyses, we looked at the microbiome response to antibiotics under high-sugar and high-fat (Western) and standard high-fiber mouse (Chow) diets in male and female C57BL/6 from Jackson Laboratory, and female mice from Charles River Laboratories. The microbiome composition of each set of mice had a distinct pre-antibiotic starting point, depending on vendor, sex, and diet. These differences were further exacerbated by antibiotic exposure and revealed that each group responded differently to this perturbation. In particular, we found that the Western diet microbiome had an exacerbated response to antibiotics with greater changes in alpha, and beta diversity, and microbial composition when compared to the antibiotic-treated Chow diet cohort. In particular, we detected blooms in Enterobacteriaceae, Streptococcaceae, and Peptostreptococcaceae that were not found in the Chow diet. The response to antibiotics on each diet also appeared to be vendor and sex dependent. Charles River female mice had less Bifidobacteriaceae, Clostridia_UCG.014, and Clostridiaceae compared to Jackson Laboratory females in a Western diet, while female mice had more Bacteroides, Bilophila, and Parasutterella compared to male mice. In a narrow sense, these findings underscore the importance of considering vendor source, diet, and sex when examining antibiotics’ impact on mice. The broader implications suggest that we will likely need to utilize patient-specific microbiome-informed approaches in the development of human therapeutics to safeguard the microbiome during antibiotic exposure.